Bridging the Philosophy of Science and Architecture: An Analysis Through Sou Fujimoto - Nanqi Ye; Minglu Zhang; Jianming Su (Buildings)
Architecture in each era is profoundly shaped by its prevailing scientific and technological context, just as architects’ intellectual frameworks are influenced by contemporaneous philosophies of science. Since the 19th century, rapid scientific and technological advances have coincided with the parallel development of scientific–philosophical thought, giving rise to the modern and postmodern architectural movements. This paper reviews a century’s philosophy of science development and traces its impact on architectural thought, mapping the co-evolution of “philosophy of science—architecture” within a historical timeline and highlighting key paradigm shifts. It then investigates how technology and philosophies of science leverage architecture as a mediator to advance their own evolution. Through a comparative case study of Sou Fujimoto’s design theories and projects, this paper elucidates the mechanisms, constraints, and logical progression linking scientific philosophy and architectural practice. Finally, on the basis of these mechanisms, the paper offers a concise discussion of future directions in architectural thought under the influence of emerging technologies, such as artificial intelligence and self-media, indicating how the next paradigm may emerge at the intersection of technological innovation, ecological responsibility, and human-centred design.